2013
DOI: 10.3390/cryst3010001
|View full text |Cite
|
Sign up to set email alerts
|

Is the Registry Between Adjacent Graphene Layers Grown on C-Face SiC Different Compared to That on Si-Face SiC

Abstract: Abstract:Graphene grown on C-face SiC substrates using two procedures, high and low growth temperature and different ambients, was investigated using Low Energy Electron Microscopy (LEEM), X-ray Photo Electron Electron Microscopy (XPEEM), selected area Low Energy Electron Diffraction (μ-LEED) and selected area Photo Electron Spectroscopy (μ-PES). Both types of samples showed formation of μm-sized grains of graphene. The sharp (1 × 1) μ-LEED pattern and six Dirac cones observed in constant energy photoelectron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 23 publications
4
21
1
Order By: Relevance
“…Rotational disorder was observed, which was concluded from the sharp (1ˆ1) µ-LEED patterns. Additionally, only six Dirac cones centered around the K-points in the Brillouin zone appeared in the constant energy photoelectron angular distribution patterns Ei(kx,ky), recorded from grains with two, three and four graphene monolayers grown at lower temperatures (1400-1500C) [139]. High mobilities are present in the graphene layers sandwiched between the underlying and overlaying conducting layers [137].…”
Section: Growth Of Graphene On C Facementioning
confidence: 99%
See 2 more Smart Citations
“…Rotational disorder was observed, which was concluded from the sharp (1ˆ1) µ-LEED patterns. Additionally, only six Dirac cones centered around the K-points in the Brillouin zone appeared in the constant energy photoelectron angular distribution patterns Ei(kx,ky), recorded from grains with two, three and four graphene monolayers grown at lower temperatures (1400-1500C) [139]. High mobilities are present in the graphene layers sandwiched between the underlying and overlaying conducting layers [137].…”
Section: Growth Of Graphene On C Facementioning
confidence: 99%
“…Rotational disorder was observed, which was concluded from the sharp (1 × 1) µ-LEED patterns. Additionally, only six Dirac cones centered around the K-points in the Brillouin zone appeared in the constant energy photoelectron angular distribution patterns Ei(kx,ky), recorded from grains with two, three and four graphene monolayers grown at lower temperatures (1400-1500C) [139]. Figure 28. (a) C 1s spectra collected, using a probing area of 4 µm, from domains with different graphene thickness; (b-g) show 1.5 µm selected area LEED patterns; (b,c) the one ML domain at 45 and 145 eV; (d,e) the two ML domain at 45 and 145 eV; and (f,g) the four ML domain at 45 and 130 eV, respectively.…”
Section: Growth Of Graphene On C Facementioning
confidence: 99%
See 1 more Smart Citation
“…So far, no one has reported C-face graphene samples to contain an ordered carbon buffer layer like on the Si-face. PES studies did not find any trace of such a carbon interface layer [41,70,71]. Only some TEM and LEEM studies have reported the presence of a disordered carbon interface layer [67][68][69].…”
Section: Graphene Grown On C-face Sicmentioning
confidence: 99%
“…Therefore, graphene grown on C-face appeared more promising for certain electronics applications if its thickness and uniformity could be controlled/improved. Also for the C-face growth in an Ar ambient, and/or in a graphite confinement, has been reported [66,70,71,75] to provide considerable improvement in the graphene quality but similar uniformity and large domain/grain sizes as on Si-face SiC has so far not been possible to accomplish.…”
Section: Graphene Grown On C-face Sicmentioning
confidence: 99%